2022
DOI: 10.1155/2022/2538807
|View full text |Cite|
|
Sign up to set email alerts
|

GRUBin: Time-Series Forecasting-Based Efficient Garbage Monitoring and Management System for Smart Cities

Abstract: The waste management of an evolving smart city environment is one of the most important tasks as the living conditions and health of the population depend on proper waste management. Currently deployed systems are failing to monitor the garbage production as they use IoT-based pipelines to monitor the production in a locality, but often the device is used to get destroyed by the frequent use of dustbin. This leads to an increase in expenditure and affects the sustainability of the system. In this work, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Urban resource management: lighting, waste management and water supply Belsare et al, 2023;Mishra et al, 2022;Malik et al, 2023;Gupta et al, 2022…”
Section: Urban Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban resource management: lighting, waste management and water supply Belsare et al, 2023;Mishra et al, 2022;Malik et al, 2023;Gupta et al, 2022…”
Section: Urban Resource Managementmentioning
confidence: 99%
“…This is addressed through the use of IoT for waste monitoring, a network of wireless sensors for data communication, and discrete wave transformations, image processing, and machine learning for image categorization (Cvitić et al, 2021). Additionally, a route based on the classification of container stations is proposed, considering temporal and spatial data on filling times and route locations to minimize collection time through the creation of an efficient garbage collection algorithm (Mishra et al, 2022).…”
Section: Urban Resource Management: Lighting Waste and Water Supplymentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%